Antara Kasih Karunia dan Tanggung Jawab: Kajian Teologis Filipi 2:12 - Saputra, Yosua Dwi; Lucas Tjong , Andrew; Binar, Sri (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2025)
Philippians 2:12 (KJV), which contains the exhortation “work out your own salvation with fear and trembling,” often serves as a focal point of debate in theological discussions regarding the relationship between God’s grace and human responsibility. This paper aims to theologically examine the nature of the relationship between grace and responsibility as reflected in this verse, employing contextual, historical, and grammatical analysis through a hermeneutical approach. The author argues that salvation in Pauline theology is not a past event that has already occurred, but rather an ongoing process grounded in God’s initiative. The emphasis on “fear and trembling” is not a form of legalistic fear but rather an expression of reverence arising from a proper understanding of the immense grace of God. Accordingly, this verse demonstrates a synergy between God’s work and human active participation in the process of salvation; although distinguishable, they cannot be separated or confused. This study is relevant for a balanced Christian understanding of faith that integrates both grace and responsibility.